2018
DOI: 10.1016/j.ihj.2018.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Role of three dimensional transesophageal echocardiography in predicting mitral regurgitation after percutaneous balloon mitral valvuloplasty

Abstract: BackgroundPercutaneous balloon mitral valvuloplasty (PBMV) can be complicated with significant mitral regurgitation (MR). We performed a pilot, prospective study to evaluate the role of three dimensional transesophageal echocardiography (3D-TEE) in the prediction of MR after PBMV through mitral valve quantification (MVQ).MethodsBetween October 2014 and October 2016, 37 patients with rheumatic, moderate-to-severe mitral stenosis, referred to the Cath lab of Bab Alshearia University hospitals for PBMV, were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Echocardiographic information including degree and symmetry of commissural calcification have been reported to be predictive for MR deterioration ( 24 , 30 ). Novel parameters derived from the three-dimensional transesophageal echocardiography such as scallop tenting, prolapse volumes or heights of coaptation may be useful for predicting severe MR after PBMV ( 31 , 32 ). Other imaging modalities such as cardiac magnetic resonance imaging may provide additional information on calcium distribution and can be less operator dependent ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic information including degree and symmetry of commissural calcification have been reported to be predictive for MR deterioration ( 24 , 30 ). Novel parameters derived from the three-dimensional transesophageal echocardiography such as scallop tenting, prolapse volumes or heights of coaptation may be useful for predicting severe MR after PBMV ( 31 , 32 ). Other imaging modalities such as cardiac magnetic resonance imaging may provide additional information on calcium distribution and can be less operator dependent ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study showed that multitrack balloon technique can significantly improve MS as proved by significant reduction of the means of gradient pressure, RVSP, and LA pressure. Actually, PMV is an effective procedure for MS with any of its technique either by Inoue balloon, metallic commissurotome, or multitrack double balloon as reported by Sharieff et al [9], Sherif et al [10], Sowdagar and Subba [11], Alkhouly et al [12].…”
Section: Discussionmentioning
confidence: 99%